New Insights Into the Regulation of Lipoprotein Metabolism by PCSK9: Lessons From Stable Isotope Tracer Studies in Human Subjects - Ying, Qidi; Chan, Dick C.; Watts, Gerald F. (Frontiers in Physiology, 2021)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a convertase enzyme mostly produced by the liver. It is a key regulator of LDL metabolism because of its ability to enhance degradation of the LDL receptor. PCSK9 also regulates the metabolism of lipoprotein(a) [Lp(a)] and triglyceride-rich lipoproteins (TRLs). Its key role in modulating atherosclerotic cardiovascular disease (ASCVD) is supported by genetic studies and clinical outcome trials. Kinetic studies provide mechanistic insight into the role of PCSK9 in regulating the physiology and pathophysiology of plasma lipids and lipoproteins. Kinetic data have demonstrated that plasma PCSK9 concentration is inversely associated with the clearance of LDL in men. Gain-of-function mutations of PCSK9 markedly increase plasma LDL-cholesterol concentrations due to impaired LDL-apoB catabolism. Conversely, PCSK9 deficiency results in low LDL-cholesterol associated with enhanced LDL-apoB clearance. Inhibition of PCSK9 with monoclonal antibodies (such as evolocumab or alirocumab) lowers plasma LDL-cholesterol and apoB levels chiefly by upregulating the catabolism of LDL particles in healthy indviduals. As monotherapy, PCSK9 inhibitor reduced Lp(a) concentrations by decreasing the production rate. However, as combination therapy, it reduced the plasma concentration of Lp(a) by increasing the fractional catabolism of Lp(a) particles. In statin-treated patients with high Lp(a), PCSK9 inhibition lowers plasma Lp(a) concentrations by accelerating the catabolism of Lp(a) particles. The effect of PCSK9 inhibition on TRL metabolism has been studied in healthy individuals and in patients with type 2 diabetes. These findings suggest that PCSK9 appears to play a less important role in TRL than LDL metabolism. Kinetic studies of PCSK9 inhibition therapy on lipoprotein metabolism in diverse high risk patient populations (such as familial hypercholesterolemia) and new therapeutic combination also merit further investigation.